Optimalisasi Potensi Ubi Jalar di Desa Sindang Karya Kecamatan Menes, Kabupaten Pandeglang - Encep Andriana; Indhira Asih Vivi Yandari; Ratna Sari Dewi; Callista Aulina; Suci Ramadayanti; Tri Esti Noviyanti (Jurnal Pengabdian Pada Masyarakat, 2020)
OPTIMIZING THE SWEET POTATOES’ POTENTIAL IN SINDANGKARYA VILLAGE, MENES SUB-DISTRICT, PANDEGLANG REGENCY. Sweet potato is one of the agricultural commodities that is suitable for cultivation in Sindangkarya village, Pandeglang Regency. Each year, Sindangkarya village produces 350 tonnes of sweet potato. However, the low price of sweet potato causes small income for the residents. One of the efforts to increase its selling value is processing sweet potatoes into various products such as sweet potato cake or various other processed products. The problem founded is that people do not have the knowledge and skills of sweet potatoes utilization. The purpose of this community service activity is to transfer knowledge and train the community skills in processing sweet potatoes so they will have a higher selling value and attract the buyers. This article concludes that Sindangkarya Village has a business potential that involves the participants, PKK Cadres, Posyandu Cadres and Youth Organization developing creative ideas to make valuable products and beneficial to the lives of Sindangkarya residents and can reduce unemployment.